Pre-urban settlements in Western Lithuania 10th-13th century - Genys, Jonas (Hikuin, 1998)
The question of the origin of towns in Lithuania is still subject to scholarly discussion. In the early literature of the history of European towns only a few Baltic trade and craft centres are mentioned, examples are Truso, Grobina and Kaup (Viskiautai). However, the latest research by Eastern Baltic archaeologists has shown that the problem of origin of towns and their location in the region inhabited by the Balts is far more complex, and the number of pre-urban trade- and craft centers much greater; than previously thought. The purpose of this contribution is, based on the latest archeological research, to establish the date of the foundation of pre-urban settlements in Western Lithuania (the Western Baltic cultural zone), to describe the structure of the settlements, and to locate their remains.